First versus second stage caesarean section: a comparison of maternal and neonatal outcomes - Sinha, Sushma; Malik, Surya; Dixit, Mala (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: A retrospective study was done to compare the maternal and neonatal complications of caesarean delivery performed in the second stage compared with the first stage of labor. Methods: This is a one year retrospective study done in a 100-bedded hospital, govt of NCT OF Delhi, New Delhi from 1st November 2015 to 31st October 2016. Total number of deliveries in this one year duration were 1785, including both normal and caesarean deliveries. Total number of patients who underwent caesarean delivery in the first stage of labor were 159, and in 2nd stage of labor were 15 during this time period. These were designated into two groups, group 1 and group 2. These two groups were then compared in terms of maternal demographics, labor characteristics, maternal outcomes and neonatal outcomes. Numerical variables were compared between groups by calculating P-value for each variable. P-value <0.05 was considered statistically significant. Results: Caesarean deliveries performed in the second stage were associated with increased maternal morbidity in terms of blood loss, unintended extensions, blood transfusions, prolonged hospital stay, febrile morbidity. Similarly, Neonatal morbidity was much higher in the patient who underwent LSCS in 2nd stage of labor compared to 1st stage. There was increase in neonatal complications, for e. g. –5 minute Apgar <7, NICU admissions >24 hrs, neonatal septicaemia, (P-value <0.05). Conclusions: In conclusion, present study suggests that women undergoing caesarean section in the second stage of labor have increased maternal and fetal morbidity. Therefore, selection of birthing method should be made very carefully and meticulously to decrease maternal and neonatal morbidity.